TEKNIK PELAKSANAAN PROGRAM SAHABAT PERPUSTAKAAN DI SMA NEGERI 1 GUNUNGHALU KAB. BANDUNG BARAT - R, Dede Hani; Sinaga, Dian; Rosfiantika, Evi (Jurnal Kajian Informasi dan Perpustakaan, 2014)
This study discusses the Design of "Library Friend" Program in the School Library Development at the Library of SMA Negeri 1 Gununghalu. The purpose of this study is to determine human resource management, the activities and techniques of "Library Friend" program implementation. The method used is a qualitative method of action research. The data were collected by interview, observation, library research and the collection of documentation. The Informants in this study are the coordinator of the library, library staff, teachers, and the students of SMAN 1 Gununghalu. The members involved in the program are the students and the library staff. The activities of the program are making competitions, such as: reading poetry competition, scientific work competition, storytelling, writing Sundanese short stories contest (culture), and an exhibition of the library. The technical implementation of the Library Friend program will have several stages of implementation such as: socialization, counseling together, inauguration, work-meeting, the implementation of activities, job evaluation and work reports of the Library Friend program.Â  Penelitian ini membahas Desain Program "Perpustakaan Teman" dalam Pengembangan Perpustakaan Sekolah di Perpustakaan SMA Negeri 1 Gununghalu. Tujuan dari penelitian ini adalah untuk menentukan manajemen sumber daya manusia, kegiatan dan teknik pelaksanaan program "Perpustakaan Teman". Metode yang digunakan adalah metode kualitatif penelitian tindakan. Data dikumpulkan melalui wawancara, observasi, studi pustaka dan pengumpulan dokumentasi. The Informan dalam penelitian ini adalah koordinator perpustakaan, staf perpustakaan, guru, dan siswa SMAN 1 Gununghalu. Anggota yang terlibat dalam program ini adalah mahasiswa dan staf perpustakaan. Kegiatan dari program ini membuat kompetisi, seperti: kompetisi membaca puisi, lomba karya ilmiah, cerita, menulis Sunda cerita lomba pendek (budaya), dan pameran perpustakaan. Teknis pelaksanaan program Teman Perpustakaan akan memiliki beberapa tahapan implementasi seperti: sosialisasi, konseling bersama-sama, peresmian, pertemuan, pelaksanaan kegiatan, evaluasi pekerjaan dan laporan kerja dari program Perpustakaan Teman.